Effects of yacon on carbohydrates and lipid metabolism, oxidative-nitrative stress markers changes in rats with experimental metabolic syndrome - Mariia Nagalievska; Khrystyna Vilkiv; Lidiya Mishchenko; Nataliia Sybirna (Heliyon)
Background and aim: Smallanthus sonchifolius (Poepp. and Hendl.) H. Robinson, commonly known as yacon, is a medicinal species recognized for its therapeutic properties. The hypoglycemic and hypolipidemic effects of yacon root tubers have been well-documented across various models of metabolic syndrome. However, research on the effects of biologically active compounds derived from yacon leaves remains limited. The aim of the study was to evaluate the hypoglycemic, hypolipidemic and antioxidant effects of an aqueous extract of yacon leaves under the fructose-induced experimental metabolic syndrome. Experimental procedure: In the study were used male Wistar white rats, in which metabolic syndrome was induced by consuming a 10 % fructose solution. Animals were given an aqueous extract of yacon leaves at a dose of 500 mg per kilogram of body weight for seven and fourteen days following the establishment of metabolic syndrome. Hypoglycemic (glucose and glycosylate hemoglobin concentrations) and hypolipidemic (plasma cholesterol, triglycerides, low-density lipoproteins and high-density lipoproteins levels) effects and antioxidant activity (activity of superoxide dismutase, catalase, glutathione peroxidase, NO-synthase, the content of nitrite anion (NO₂‾) and nitrate anion (NO₃‾), content of carbonyl groups and thiobarbituric acid reactive substances) of extract were then evaluated. Results: The 14 days use of aqueous extract of yacon for the treatment of fructose-induced metabolic syndrome leads to a decrease of animals’ body weight (59.94 %), glucose concentration (10.33 %), glycosylated hemoglobin content (61.58 %), blood plasma triglycerides (50.35 %), cholesterol (24.46 %), low-density lipoproteins (21.56 %), as well as to increase in high-density lipoproteins concentration (29.29 %), paraoxonase activity (56.03 %). In animals with experimental MetS yacon cause oxidative-nitrative stress indicators normalization: increase in SOD (47.85 %) and GPO activity (16.55 %); decrease in TBARS content (23.77 %) and proteins oxidative modification products of neutral character (52.56 %); decrease in NOS activity (12.30 %), which was accompanied by a decrease in nitrate content (10.44 %). Conclusions: The aqueous extract of yacon demonstrates significant hypoglycemic and hypolipidemic effects in a fructose-induced model of experimental metabolic syndrome, contributing to the normalization of both prooxidant and antioxidant states in rat erythrocytes.